L’expérience du raccrochage scolaire : Apprendre à dire et à faire entendre l’événement du décrochage pour le penser, le dépasser et en faire son histoire - Valérie Melin (Université de Provence, 2020)
This article questions the pedagogical accompaniment of reschooling by analyzing the function and the stakes of a narration of the drop-out event through the presentation of a research-intervention carried out with young former drop-outs, students at the Micro-Lycée of Sénart. The approach of investigation by interviews is based on the theoretical frameworks of the biographical research in education which defines the approach of self-storytelling as a biographical work which allows the individual, in the conditions of his social experience, to integrate, structure, interpret the situations and the events of his existence. This article explores both the clinical and political conditions of a new relationship to oneself based on a dynamic of reflexive distancing with regard to the experience of dropping out, thus allowing the overcoming of its traumatic dimension in order to make a future possible.